Contract law : text, cases, and materials / Ewan McKendrick. - McKendrick, Ewan (Oxford University Press, 2024)
Celebrated and respected, this is the stand-alone guide to contract law. Written by Ewan McKendrick, it uses a unique balance of commentary, cases, and materials. Explaining, applying, and contextualising, it shows students the law at work and helps them to gain a thorough understanding.